Mango Firmness Modeling as Affected by Transport and Ethylene Treatments - Schouten, Rob E.; Fan, Shuang; Verdonk, Julian C.; Wang, Yuchen; Kasim, Nur Fauzana Mohd; Woltering, Ernst J.; Tijskens, L. M. M. (Frontiers in Plant Science, 2018)
More and more, tropical fruit are subjected to accelerated ripening at receiving markets until ‘ready to eat’. We propose a kinetic model that incorporates the effects of temperature and ethylene on the firmness behaviour of ‘Keitt’ and ‘Kent’ mangoes. Stiffness of individual mangoes, as measured by the acoustic firmness tester, was measured repeatedly over time. The firmness model assumes fixed levels of ethylene, established after the climacteric peak, that steadily induces production of softening enzymes that subsequently denaturalise. The initial level of these enzymes is assumed to be zero due to either the tree factor for freshly harvested mangoes, or due to chilling injury for reefer transported mangoes. The kinetic parameter set for ‘Keitt’ mangoes was estimated based on a Spanish batch, freshly harvested and ripened under dynamic temperature scenarios, combined with a reefer transported Brazilian batch stored at four constant temperatures. Firmness data from reefer transported batches, from Brazil, Ivory Coast and Mali, stored at four constant temperatures were used to estimate a set of kinetic parameters for the ‘Kent’ mangoes. Only a partial set of ‘Kent’ kinetic parameters could be established due to the often already advanced stage of softening at the time of arrival. The effect of ethylene was investigated by applying external ethylene levels, varying from 0-100 µL L-1. The effect of external application of ethylene was modelled by estimating EF, the ethylene factor, being a reflection of the internal ethylene level and ethylene sensitivity. The effect of ethylene application on softening was sometimes huge. For an Israeli ‘Keitt’ batch a fifty times higher EF was found when the firmness behaviour of low- (without ethylene application) and high temperature (with ethylene application) stored sub-batches were compared. However, this effect was sometimes also small, especially for reefer transported mangoes. For commercial application, a reliable prediction of the time until ‘ready to eat’ is not possible because of the current inability to assess EF. Nevertheless, the proposed model described mango softening accurately, irrespective of the sourcing area and includes the effects of storage temperature and ethylene application.